Incidence of travel: recent journeys in ancient South America - Moore, Jerry D., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
Drawing on personal experience and historical and archaeological studies from across South America, Moore introduces readers to archaeological sites and remains to describe what it's like to be in the field and facilitating critical thinking about what these places might have been like in the past .--Provided by publisher.
Incidence of travel -- Making mounds -- La caminata -- River of paintings -- Land lines -- To the lost city -- Avenue of the volcanoes -- Measuring the cosmos -- Following Pizarro -- Epilogue: backwards in Bolivia.
Keywords: Moore, Jerry D. -- Travel -- South America; South America -- Antiquities; South America -- Description and travel